(untitled) (Journal of Computational Mathematics, 1993)
This paper presents a random numerical method which combines the random vortex method and the random choice method. A random choice method is used for the modeling reaction-diffusion system. The splitting of source terms in two dimensions for the random choice method is tested. A hybrid random vortex method is used for solving the Navier-Stokes equation which governs the fluid motion. With the assumption of incompressibility, the fluid motion can be uncoupled from the chemistry. The method is applied to a flow passing a circular cylinder which is kept cold or heated. In both cases the method demonstrates an ability to resolve turbulent effects on flame front propagation.